Minimally Invasive Thyroidectomy and Intraoperative Neuromonitoring (IONM): is MIVAT the better surgical option? - Bonati, Elena; Loderer, Tommaso; Viani, Lorenzo; Donato, Valentina; De Gennaro, Flavia; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2024)
Background: In the last two decades, many new techniques have been introduced in thyroid surgery. Minimally invasive video-assisted thyroidectomy (MIVAT) has benefited from technological advances and the use of intraoperative neuromonitoring (IONM) has improved surgical outcomes, with a small cervical incision. Methods: We retrospectively analyzed the use of IONM in patients undergoing MIVAT, from 2015 to 2020, at the Operative Unit of the General Surgical Clinic of the University Hospital of Parma, Italy. We compared our data with a control group from 2011 to 2014 treated with the same minimally invasive technique but without using IONM. The aim of our study was to evaluate the use of IONM in patients undergoing MIVAT, and we compared data of the two groups, routinary use or non-use of the IONM, to assess if there was a different incidence of postoperative complications and a significant difference in surgical operative time. Results: We collected data on 328 cases, divided into two groups according to the routinary use or non-use of the IONM. The incidence of serological hypocalcemia was lower in group 2 (p <0.0001). We did not register differences in the incidence of wound infection, postoperative seroma, or hemorrhage. We did not register statistically significant differences in the surgical procedure time between the groups and the incidence of dysphonia was higher in group 1 but without statistical significance (p=ns). Conclusions: MIVAT is a feasible and safe technique with good esthetic outcomes and the combined use of IONM presents a better outcome in terms of postoperative dysphonia.